Caracterização da população de ectoparasitos em cães de núcleos de expansão urbana de Juiz de Fora, Minas Gerais, Brasil - Rodrigues, Denise F. [UNESP]; Daemon, Erik; Rodrigues, André Flávio S.F. (My University, 2008)
The present work studied the characterization of ectoparasites on dogs in the nucleus of expansão urbana of Juiz de Fora, Minas Gerais, Brazil. The collections were conducted from July to September 2003, examining 101 dogs of no defined breed. The ectoparasites were collected through visual and tactile inspection of the animals' bodies, and were then placed in bottles with 70° GL ethanol and identified under a stereomicroscope. Specimens were clarified and mounted on slides for analysis under a photonic microscope. Among the siphonaptera, Ctenocephalides felis was the most prevalent (64.35%), with mean intensity of 6.12 ± 5.37 siphonaptera/dog, followed by Rhopalopsyllus lutzi (3.96%), a hybrid of C. felis X C. canis (1.98%), and Tunga penetrans (1.98%). The only species of phthiraptera found was Trichodectes canis (7.92%), with 1.3 ± 0.51 phthiraptera/dog. Among the ixodidae, Rhipicephalus sangui-neus was the most prevalent species (49.50%), with a mean intensity of 6.44 ± 10.2 ixodidae/dog, followed by Am-blyomma cajennense (3.96%), Boophilus microplus (2.97%), A. ovale (1%) and A. aureolatum (1%). The ixodid nymphs were separated into a Amblyomminae nymphs (58.41%), with 10.11 ± 10.09 nymphs/dog, and Rhipicephalinae nymphs 1(24.75%), with 2.64 ± 3.25 nymphs/dog. Ixodid larvae were found on 3.96% of the dogs.
Characterization of ectoparasites on dogs in the nucleus of urban expansion of Juiz de Fora, Minas Gerais, Brazil
Keywords: Ixodidae; Phthiraptera; Rural zone; Siphonaptera; Ticks